Shielding Effectiveness Estimation of a Metallic Enclosure with an Off-center Aperture for Obliquely Incident and Arbitrary Polarized Plane Wave - Dan Shi; Na Lv; Yougang Gao , (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A circuit model for the shielding effectiveness (SE) estimation of a metallic enclosure is proposed, whose off-center aperture is irradiated by the obliquely incident and arbitrary polarized plane wave. This new model has advantages in the following aspects. First, it can deal with the arbitrary angular and polarized incident wave other than the normal incident wave. The incident wave angle and polarization direction are considered in the proposed analytical formulas. Second, higher-order modes such as TEmn and TMmn are included to enable the model to be applicable in higher frequencies. Third, the impedance of the enclosure wall is considered rather than the perfect conductor assumption used in the published literatures, which removes the deficiency that the aperture impedance is zero when the length of the aperture is equal to an integral number of the wavelengths. The influences on the SE from different parameters such as the incident wave angle, the polarization direction as well as the enclosure wall thickness are investigated. Finally, the accuracy of the proposed model is validated by measurements, simulations and comparisons with other literatures. The proposed method is particularly useful for the shielding enclosure design in the electronic manufacturing industry.